Resonance excitation and frequency up-conversion of plasma oscillations upon the optical breakdown of a thin film - Gildenburg, V.B.; Vvedenskii, N.V. (Вопросы атомной науки и техники, 2006)
We study the spatiotemporal evolution of the field and plasma during the optical breakdown process induced by p-polarized laser radiation in a thin gaseous layer. The computer simulation of the process based on the solution of the vector wave equation for the slow time-varying field amplitude and the known expression for the tunnel ionization rate is carried out with taking into account the spatial dispersion caused by the thermal motion of electrons. It is found that generation of the plasma waves during the transition through the plasma resonance points in the layer affects strongly the dynamics of breakdown process and the spectrum of reflected and transmitted radiation.